Quelle multifonctionnalité des transhumances urbaines de brebis ? - Christian Nicourt; Jacques Cabaret (VertigO)
The cattle and sheep seasonal change to summer pastures has offered cheap feed to the farmers. These summer natural pastures are the property of the regions. They are regrouped in Valley’s syndicates and are available for local farmers free of charge. The sheep transhumances in France are practised in the Crau plaine (South-east France) and the Basque region (South-west France). These classical transhumances are still used but since 2010, other types of transhumances appeared, mixing social perspectives and shows. Thus transhumances become more urban and were included in towns’ feasts. How this change from a transhumance for practical purposes to a show transhumance did occur ? Who did participate to this change ? How transhumances become multifunctional ?